2021
DOI: 10.1038/s41598-021-99858-w
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oropharyngeal dysphagia in geriatric patients and real-life associations with diseases and drugs

Abstract: Risk factors for oropharyngeal dysphagia (OD) in elderly patients are mainly central nervous system (CNS) and structural organic diseases or presbyphagia. We analysed the OD prevalence and association of OD with multimorbidity and polypharmacy using real-life data to complete this spectrum, with a focus on further and iatrogenic risk. This was a cross-sectional retrospective study based on a random sample of 200 patients admitted to a geriatric hospital. Data analysis included diagnoses, the detailed list of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 56 publications
(53 reference statements)
2
33
0
3
Order By: Relevance
“…The data collected in this study showed that in physiological (high level of ECM in control CPM) and pathological (excessive ECM deposition in OPMD CPM) human muscle fibrosis, the populations of FAPs involved were globally similar, indicating that TGFβ and ET‐1 are broadly implicated in human muscle fibrosis. It is known that increase in connective tissue can eventually lead to dysphagia in the elderly: dysphagia is known to affect about 15–30% of aged individuals 39 . In our observations, this connective tissue is increased in OPMD patients, and consequently, the fibrosis would have a negative effect causing a stiffening of the tissue and problems in deglutition.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…The data collected in this study showed that in physiological (high level of ECM in control CPM) and pathological (excessive ECM deposition in OPMD CPM) human muscle fibrosis, the populations of FAPs involved were globally similar, indicating that TGFβ and ET‐1 are broadly implicated in human muscle fibrosis. It is known that increase in connective tissue can eventually lead to dysphagia in the elderly: dysphagia is known to affect about 15–30% of aged individuals 39 . In our observations, this connective tissue is increased in OPMD patients, and consequently, the fibrosis would have a negative effect causing a stiffening of the tissue and problems in deglutition.…”
Section: Discussionsupporting
confidence: 49%
“…It is known that increase in connective tissue can eventually lead to dysphagia in the elderly: dysphagia is known to affect about 15–30% of aged individuals. 39 In our observations, this connective tissue is increased in OPMD patients, and consequently, the fibrosis would have a negative effect causing a stiffening of the tissue and problems in deglutition. Further studies are needed to decipher specific changes in muscle‐associated fibrosis in pathological conditions like OPMD (Table S2 ).…”
Section: Discussionsupporting
confidence: 46%
“…The diagnostic tool for OD in most studies was physical examination (12 articles) or volume–viscosity swallow test (10 articles). The highest quality assessment score based on the JBI checklist was related to the study of Wolf et al [ 23 ] with a score of 9. Table 2 represents the characteristics of studies included in the systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The highest prevalence rate of OD (96%) was reported in the study of Almeida et al [ 22 ] and the lowest rate (7.3%) in the study of Watson and Lally [ 21 ]. The highest quality assessment score based on JBI checklist criteria was related to the study of Wolf et al [ 23 ], which reported the prevalence rate of OD as 29%.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacotherapy, however, produces limited results and should therefore not be used as a stand-alone treatment, but rather as an adjunct to other therapies [8] . Furthermore, medications such as antidopaminergic agents, anticholinergic drugs, or benzodiazepines induce or exacerbate dysphagia [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%